A review on the recent advances in binder-free electrodes for electrochemical energy storage application. (June 2022) - Gerard, Ong; Numan, Arshid; Krishnan, Syam; Khalid, Mohammad; Subramaniam, Ramesh; Kasi, Ramesh
Abstract: Progress in portable electronics has catalysed the research for developing efficient electrochemical energy storage devices. Recently, binder-free synthesis techniques have been introduced, enhancing the values of the electrochemical performance parameters of the materials closer to their theoretical values. Among various binder-free synthesis techniques such as chemical vapour deposition (CVD), electrophoretic deposition (EPD), inkjet printing, electrostatic spray deposition (ESD), sputtering, etc., microwave-assisted hydrothermal synthesis is attaining significant attention from the scientific community due to lower cost, environmental friendliness, and lower reaction time. This review focuses on fabricating binder-free electrodes using microwave-assisted hydrothermal synthesis and compares its advantage with the conventional hydrothermal route for electrochemical energy storage applications. Further, the review critically analyses the commercial viability of microwave-assisted hydrothermal fabrication of the electrodes for electrochemical energy storage devices. Finally, the review identifies the research gap and future opportunities in the binder-free approach to fabricate electrodes for electrochemical energy storage devices. Highlights: Binder-free synthesis enhances the electrochemical performance of the materials. Binder-free electrodes fabrication using microwave-assisted hydrothermal synthesis. Microwave-assisted synthesis advantages over conventional routes for EES. Microwave-assisted hydrothermal fabrication viability of electrodes for EES devices. Opportunities in the binder-free approach to fabricate electrodes for EES devices.